2022
DOI: 10.1002/aps3.11476
|View full text |Cite
|
Sign up to set email alerts
|

Development of a petal protoplast transfection system for Sinningia speciosa

Abstract: Premise Transient gene expression systems are powerful tools for studying gene interactions in plant species without available or stable genetic transformation protocols. We optimized a petal protoplast transformation protocol for Sinningia speciosa, a model plant, to study the development of floral symmetry. Methods and Results A high yield of petal protoplasts was obtained using a 6‐h enzyme digestion in a solution of 1.5% cellulase and 0.4% macerozyme. Modest transfection efficiency (average 41.4%) was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The choice of materials for isolating plant cell protoplasts plays a pivotal role in determining both the yield and viability of the resulting protoplasts [4]. Commonly employed materials for protoplast isolation include young leaves [5], petals [6], roots [7], callus [8], and suspension cultures [9]. And it has been shown that vigorously growing and younger tissues used as isolation materials tend to yield protoplasts with higher yields and vitality [10].…”
Section: Protoplast Isolation 21 Plant Tissues For Protoplast Isolationmentioning
confidence: 99%
“…The choice of materials for isolating plant cell protoplasts plays a pivotal role in determining both the yield and viability of the resulting protoplasts [4]. Commonly employed materials for protoplast isolation include young leaves [5], petals [6], roots [7], callus [8], and suspension cultures [9]. And it has been shown that vigorously growing and younger tissues used as isolation materials tend to yield protoplasts with higher yields and vitality [10].…”
Section: Protoplast Isolation 21 Plant Tissues For Protoplast Isolationmentioning
confidence: 99%